ACOPIO: Cuba's State Procurement and Distribution Agency - José Alvarez (EDIS)
One of the reasons for the food scarcity in Cuba, especially that related to perishable and non-perishable agricultural product wastes, falls on Acopio, the state collection and distribution agency. This fact sheet summarizes the role of this state agency since the early days of the Cuban revolution along with its inefficiencies and reorganizations. This is EDIS document FE484, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published July 2004.